Express method for assessing proteolysis in cheese and aromatic addi- tives with cheese flavor - D. S. Myagkonosov; D. V. Abramov; E. G. Ovchinnikova; V. N. Krayushkina (Пищевые системы)
The method based on the determination of the amount of active amino groups using o-Phthaldialdehyde (OPA method) can be applied in practice to assess accurately the degree of proteolysis in cheeses. The work establishes that the OPA method gives results that strictly correlate (R2 > 0.80, p < 0.01) with the results of assessing the degree of proteolysis by the Kjeldahl method. The results of the OPA method, expressed in the absorption intensity of the colored sample at a wavelength of 340 nm (OD340), can be converted to the content of soluble nitrogenous substances in cheese (WSN), using the calibration relationship between these indicators.The accuracy of the calibration relationship between WSN and OD340 can be increased (R2 > 0.91, p< 0.01) when using the OPA method in relation to a homogeneous group of cheeses produced by the same technology using the same type of milk clotting enzyme and lactic acid starter culture and having a similar shape of the molecular mass distribution of proteolysis products.The OPA method can be used to assess the content of proteolysis products, which form cheese flavor, in EMС. The results of assessing the degree of proteolysis by the OPA method (OD340) are proportional to both the total content of soluble nitrogen and the proportion of nitrogenous substances in it with a mass of less than 0.5 kDa, which make the greatest contribution to the formation of cheese flavor.The advantage of using the OPA method for assessing proteolysis in cheeses and EMC instead of the Kjeldahl method is a simpler measurement procedure and the possibility of studying more samples in less time.